Enhanced second harmonic generation from a plasmonic Fano structure subjected to an azimuthally polarized light beam. (17th January 2018) - Shang, Wuyun; Xiao, Fajun; Han, Lei; Premaratne, Malin; Mei, Ting; Zhao, Jianlin
Abstract: We show that an azimuthally polarized beam (APB) excitation of a plasmonic Fano structure made by coupling a split-ring resonator (SRR) to a nanoarc can enhance second harmonic generation (SHG). Strikingly, an almost 30 times enhancement in SHG peak intensity can be achieved when the excitation is switched from a linearly polarized beam (LPB) to an APB. We attribute this significant enhancement of SHG to the corresponding increase in the local field intensity at the fundamental frequency of SHG, resulting from the improved conversion efficiency between the APB excitation and the plasmonic modes of the Fano structure. We also show that unlike LPB, APB excitation creates a symmetric SHG radiation pattern. This effect can be understood by considering an interference model in which the APB can change the total SHG far-field radiation by modifying the amplitudes and phases of two waves originating from the individual SRR and nanoarc of the Fano structure.